Prosurvival Bcl-2 proteins stabilize pancreatic mitochondria and protect against necrosis in experimental pancreatitis - Sung, Kai-Feng (Exp Cell Res, 2009)
Acinar cells in pancreatitis die through apoptosis and necrosis, the roles of which are different. The severity of experimental pancreatitis correlates directly with the extent of necrosis and inversely, with apoptosis. Apoptosis is mediated by the release of cytochrome c into the cytosol followed by caspase activation, whereas necrosis is associated with the mitochondrial membrane potential (ΔΨm) loss leading to ATP depletion. Here, we investigate the role of Bcl-2 proteins in apoptosis and necrosis in pancreatitis. We found up-regulation of prosurvival Bcl-2 proteins in pancreas in various experimental models of acute pancreatitis, most pronounced for Bcl-xL. This up-regulation translated into increased levels of Bcl-xL and Bcl-2 in pancreatic mitochondria. Bcl-xL/Bcl-2 inhibitors induced ΔΨm loss and cytochrome c release in isolated mitochondria. Corroborating the results on mitochondria, Bcl-xL/Bcl-2 inhibitors induced ΔΨm loss, ATP depletion and necrosis in pancreatic acinar cells, both untreated and hyperstimulated with CCK-8 (in vitro pancreatitis model). Together Bcl-xL/Bcl-2 inhibitors and CCK induced more necrosis than either treatment alone. Bcl-xL/Bcl-2 inhibitors also stimulated cytochrome c release in acinar cells leading to caspase-3 activation and apoptosis. However, different from their effect on pronecrotic signals, the stimulation by Bcl-xL/Bcl-2 inhibitors of apoptotic responses was less in CCK-treated than control cells. Therefore, Bcl-xL/Bcl-2 inhibitors potentiated CCK-induced necrosis but not apoptosis. Correspondingly, transfection with Bcl-xL siRNA stimulated necrosis but not apoptosis in the in vitro pancreatitis model. Further, in animal models of pancreatitis Bcl-xL up-regulation inversely correlated with necrosis, but not apoptosis. Results indicate that Bcl-xL and Bcl-2 protect acinar cells from necrosis in pancreatitis by stabilizing mitochondria against death signals. We conclude that Bcl-xL/Bcl-2 inhibition would aggravate acute pancreatitis, whereas Bcl-xL/Bcl-2 up-regulation presents a strategy to prevent or attenuate necrosis in pancreatitis.